La parentalité gitane et l’espace urbain : une relation renouvelée ? - David Giband (EchoGéo)
This article explores the ways in which a new kind of gypsy parenthood is expressed in a gypsy neighborhood in Perpignan. The aim is to understand how the relationship to space plays a driving role in the emerging forms of parenthood among young couples. The chosen neighborhood, Saint-Jacques, an emblematic place of the city's gypsy community, is undergoing changes driven by the public authorities but also by families. Beyond the singularities specific to sedentary Gypsies, this example shows the way in which the exercise of parenthood in working-class neighborhoods is carried out and renewed, and the central place that the spatial dimension holds.